"Think With Me:" David Carr's Enduring Invitation. (April 2016) - Sheppard, Beverly; Semmel, Marsha; Bossert, Carol
Abstract : David Wildon Carr (1945–2016) was recognized in the international cultural community as a scholar and instigator whose critical thinking challenged museum practitioners to reflect on the purpose and responsibility of their work. In his recent papers and lectures, he argued that those discussing museum experiences are late to enter into a dialogue already in progress—a dialogue which carefully considers the whole person in a community, and wherein thinking with a museum is an enterprise embedded in the learner's experience. This forum, written by three museum professionals in response to his recent untimely death, is intended to capture personal impressions of Carr's contribution to the continuing work of museums. Each author quotes from Carr's writings, since his words have such enduring strength—a strength that will continue to resonate long into the future. Each also offers readers some personal background on his work as a teacher.